Features of the pharmacological activity of polypeptide modulators on acid-sensitive ion channels in the experiment - Igor A. Dyachenko; Arkadii N. Murashev (Belgorod National Research University, 2019)
Introduction: TRPV1 receptors play a significant physiological role. To study pharmacological activity of new agonists and antagonists is important for the development of new drugs. This paper reports on the features of polypeptide antagonists of TRPV1 based on in vivo data. Materials and methods: The study was performed on 250 mature white ICR male mice weighing 25-30 g. Tests were conducted to evaluate the pharmacological activity and biological properties of APHC1-3 and a hybrid polypeptide A13 in thermal pain,, inflammation and body temperature tests. Results and discussion: APHC1-3 polypeptides showed significant antinociceptive and analgesic activity in the dose range of 0.01-0.1 mg/kg, without causing hyperthermia. A single substitution of the aspartic acid residue of АРНС1 polypeptide at position 23 by transferring one asparagine residue from the cognate peptide АРНС3 led to a significant change in the properties of the molecule. A new polypeptide A13 did not alter the thermal sensitivity of the mice, but showed the most significant analgesic activity in the acid-induced pain model, unlike АРНС1. A13 inhibits TRPV1 and affects body temperature as a classic antagonist of this receptor. Conclusion: Antagonistic properties of A13 became different from the properties of both initial analgesic polypeptides. Polypeptides APHC1-3 can be referred to as a new class of modulators of TRPV1, which produce a pronounced analgesic effect without hyperthermia.